Desperation in death [large type] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel, 2022)
"New York, 2061. The place called the Pleasure Academy is a living nightmare where abducted girls are trapped, trained for a life of abject service. Dorian, a thirteen-year-old runaway who'd been imprisoned there, might never have made it out if not for her fellow inmate Mina. Unfortunately, they didn't get away fast enough. Now Dorian is injured and Mina lies dead while Lt. Eve Dallas looks over the scene. Mina's elegant clothes and beauty products convince Dallas that she was being groomed for sex trafficking. No matter what, she must keep her head clear because she is desperate for justice and to take down those who prey on and torment the innocent"--